Pencegahan Stunting dengan Gizi Seimbang di Wilayah Sebantengan, Kelurahan Ungaran, Kecamatan Ungaran Barat, Kabupaten Semarang - Ulyanita, Istatik; Arintasari, Putri; Hastuti, Septyana Wachyu; Pranoto, Heni Hirawati (Universitas Ngudi Waluyo, 2024)
Stunting in Indonesia is a nutritional problem in children that needs attention. Stunting is a condition of failure to thrive in children under five caused by chronic malnutrition, recurrent infectious diseases, and inadequate psychosocial stimulation. The main problem in the Sebantengan area, Ungaran Village, West Ungaran District, is that out of 37 toddlers, there is 1 stunted toddler (2.7%) due to the mother's lack of knowledge about MPASI. From the problems found, an alternative solution to the problem was obtained, namely by holding an outreach activity for cadres about